Upaya Menumbuhkan Pola Pikir Anak di RA Rahmat Islamiyah Medan (Studi Kasus Pada Pembelajaran Daring) - Sahyan Sahyan; Chairani Dwi Ayu; Juliani Juliani; Sentika Yuni Sari (Al-Ulum: Jurnal Pendidikan Islam, 2020)
This study aims to determine the Efforts to Foster Children's Mindset in Online Learning Models of Early Childhood Education at RA Rahmat Islamiyah Jln Gaperta Ujung / Bakti no 25 Medan Helvetia. This research is a qualitative research, with a phenomenological research design. The method used is a qualitative method with data triangulation techniques. The research subjects in this study were 4-5 years. Based on the research, efforts to foster a child's mindset in the online learning model for early childhood education are as follows: (1) Teach children to observe objects and draw conclusions based on observations. (2) Invite children to compare two different and contrasting objects. (3) Discuss and analyze stories. (4) Teaching cooperation in fun games. (5) Ask the child to continue a story. Keywords: Mindset, Online Learning, Early Childhood